The coordinator of information and communication technologies: Its implication for open innovation - Paula Hernández-Dionis; David Pérez-Jorge; Oliver Curbelo-González; Olga Maria Alegre de La Rosa (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study aims to analyze the effects of open innovation on the figure of the Information and Communication Technologies Coordinator (ICTC) in the Higher Conservatories of Music (HCM) and Authorized Centers of Spain (ACSs). In some regions, the HCMs are regulated by the regulations applied to secondary education and that is why the figure of the CICT exists. In others, this figure does not exist and is not regulated by the administration. In the ACSs, because they are private centers, they do not exist either, although they do have persons in charge of these functions. In order to respond to the objective of this study, a tour has been made to the existing regulations, analyzing the endowment that the centers have in addition to applying a questionnaire to 27 CICT of 35 HCMs and ACSs of Spain. The results obtained reveal the lack of knowledge of this figure and the innovation it represents in its field, information on the functions and tasks of the ICTC is scarce, as is the degree of knowledge of the competencies of the latter. There is a clear need for the CICT to exist in all schools and to be regulated under a common competence framework that allows schools to progress in the same way.
Keywords: 650; Information and Communication Technologies (ICT); ICT coordinator; conservatory; music; Spain